Analysis of channel allocation and management using tlbo, ga & de algorithms in cellular networks - Mounika, M; Sharmila, Md; Prasanna Gowri, M; Tejasvi, K; Siva Ganga Prasad, M (International Journal of Engineering and Technology, 2018)
Accuracy of spectrum sensing in cellular mobile networks can be increased by reducing the sensing error probability, call blocking probability & by increasing network throughput. In our Project work, an advanced algorithms like Teaching Learning Based Optimization (TLBO), Genetic (GA) and Differential Evaluation (DE) Algorithms are used to analyze the sensing error probability, call blocking probability and network throughput. We will propose a channel allocation and management scheme with the above mentioned algorithms for supporting mobile users. With the help of these algorithms, sensing error and call blocking probabilities are analyzed to find out an optimal value for reducing the errors to some extent and improving network throughput. Channel Allocation in cellular networks is a key aspect with channel impairments and non-ideal antenna patterns. Finally, performance analysis is done through comparison of simulation results.Â